Penerapan Media Gambar pada Pembelajaran Mahārah Al-Kitābah di MA Irsyadun Nasyi’in - Zainuri Zainuri; Hilmi Mufidah Afiyatul Jannah (INAIFAS Press, 2021)
The application of image media to mahārah al-kitābah learning is a solution in learning Arabic that can be used at all levels of education. Learning mahārah al-kitābah orients students to have Arabic writing skills. One of the media that can help success in learning mahārah al-kitābah is picture media in the form of printing. This study aimed to describe the application of the image media in learning mahārah al-kitābah in class X IPS MA Irsyadun Nasyi'in Kasiyan Puger Jember by describing the learning process. The research method used was a qualitative method with data collection techniques in the form of observation, interviews, documentation, and tests. The results of the application of picture media showed that 31% of students were very capable in learning mahārah al-kitābah through the application of picture media, 42% of students were able, and 27% of students were less able in their learning. This media can be an alternative for students' success in learning mahārah al-kitābah in learning Arabic.